2014
DOI: 10.1017/s0033291714000439
|View full text |Cite
|
Sign up to set email alerts
|

Empirical evidence for discrete neurocognitive subgroups in bipolar disorder: clinical implications

Abstract: Background Recent data suggest trait-like neurocognitive impairments in bipolar disorder (BPD), with deficits about 1 s.D. below average, less severe than deficits noted in schizophrenia. The frequency of significant impairment in BPD is approximately 60%, with 40% of patients characterized as cognitively spared. This contrasts with a more homogeneous presentation in schizophrenia. It is not understood why some BPD patients develop deficits while others do not. Method A total of 136 patients with BPD complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
265
9
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(318 citation statements)
references
References 48 publications
41
265
9
3
Order By: Relevance
“…The presence of patients with mood disorders in all three clusters suggests that individual characteristics may play a more prominent role in cognitive functioning than diagnostic category. This conclusion supports the findings of previous cluster studies, which identify variable levels of cognitive impairment in samples with BD and MDD (Burdick et al, 2014;Hermens et al, 2011). The distribution of clusters identified in the present study was also similar to that revealed by other similar investigations of psychiatric samples.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The presence of patients with mood disorders in all three clusters suggests that individual characteristics may play a more prominent role in cognitive functioning than diagnostic category. This conclusion supports the findings of previous cluster studies, which identify variable levels of cognitive impairment in samples with BD and MDD (Burdick et al, 2014;Hermens et al, 2011). The distribution of clusters identified in the present study was also similar to that revealed by other similar investigations of psychiatric samples.…”
Section: Discussionsupporting
confidence: 93%
“…The hierarchical clustering procedure used in this study was similar to that described in previous investigations of similar populations (Burdick et al, 2014;Hermens et al, 2011). Patterns of neuropsychological performance were identified using Ward's method of minimum variance (Ward, 1963) with a 586 C. Cotrena et al…”
Section: Discussionmentioning
confidence: 99%
“…The drug × gene × time interactions are significant, indicating cKO mice may bear different sensitivity to methylphenidate from control, although the key point is that there were increases overall, not decreases. We did not detect severe deficits in cognitive tests, and cognition is generally reported to be more severely altered in schizophrenia than bipolar disorder (27,47). Future studies could include more sensitive and sophisticated cognitive function tests.…”
Section: Discussioncontrasting
confidence: 56%
“…(20,21). It is therefore apparent that the cognitive phenotype associated 379 with mood disorder is diverse, both in clinical settings and in the broader population.…”
Section: Effect Of Missing Data 341mentioning
confidence: 99%